Hyperrealites Online Gambling Wins on The "Pola Gacor" Content Youtube - Mustiawan, Mustiawan; Pranawukir, Iswahyu (ETTISAL : Journal of Communication, 2024)
This research aims to analyze the phenomenon of hyperreality in YouTube content which displays "gacor patterns" in online gambling. Using a qualitative approach with a critical paradigm, this study applies Roland Barthes' semiotic method to explore how visual signs and text in the content shape perception and behavior The findings show that visual signs such as the highlighting of big winning numbers, the use of bright colors, and emotional expressions of content creators, as well as provocative texts such as "gacor patterns" and "auto max win" create denotative and connotative meanings that blur the boundaries between reality and reality. Fantasy analysis reveals that this content constructs a hyperreality of winning, where the representation of a big win becomes more dominant than the actual reality. This hyperreality encourages gambling behavior in the hope of getting a similar win, which in reality is very dependent on luck. The next myth is about instilling an ideology or belief about normalizing online gambling behavior in society. This content can normalize online gambling practices and make it an activity that is accepted and desired by society. This has the potential to change the public's perception of gambling, making it appear to be a legitimate, legal, halal, and effective way to earn money. Thus ignoring the fact that online gambling is a high-risk activity that can cause significant financial losses.